Investigating Mechanical Properties of Interlocking Concrete Blocks by Recycling Waste Polyethylene Terephthalate-A Sustainable Approach - Heng, K.K. (Institute of Electrical and Electronics Engineers Inc., 2021)
Plastic consumption has increased tremendously over the years due to their versatility which enables them to be used in various industries. However, the properties of plastics which are non-biodegradable have created serious environmental problems especially polluting the oceans, harming marine organisms, and putting them at risks of extinction. At the same time, conventionally used construction materials such as clay bricks and concrete blocks also lead to other environmental issue such as the over-utilization of natural resources and emission of greenhouse gases. In current study, waste polyethylene terephthalate was used as a sand replacement in the production of interlocking concrete blocks for masonry wall application. Concrete mixtures with various percentages of PET were produced and evaluated for compressive strength and split tensile strength. In addition, microstructural characterization was also performed using Scanning Electron Microscope (SEM). The recycling of waste PET in the production of concrete interlocking blocks will produce sustainability in the construction industry. Â© 2021 IEEE.